2017
DOI: 10.1186/s12951-017-0256-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, label-free monitoring of cell viability based on cell adhesion measurements with an atomic force microscope

Abstract: BackgroundThe adhesion of cells to an oscillating cantilever sensitively influences the oscillation amplitude at a given frequency. Even early stages of cytotoxicity cause a change in the viscosity of the cell membrane and morphology, both affecting their adhesion to the cantilever. We present a generally applicable method for real-time, label free monitoring and fast-screening technique to assess early stages of cytotoxicity recorded in terms of loss of cell adhesion.ResultsWe present data taken from gold nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…We evaluated the cell viability of HeLa cells with varying concentrations 1.5, 3, 6 and 12 nM by resazurin tests and using a real-time monitoring system ( Table 2) demonstrated that the NPs are expected to be ingested by cells via receptor-mediated endocytosis. 59 The results of the B-values obtained from the real-time cell viability measurements are between 3 × 10 −5 s −1 and 7 × 10 −5 s −1 , indicating high cell biocompatibility compared with the results of Yang et al 39 The B-value findings are in the range of PEGylated Au NPs of the same size which are known to be biocompatible. Both test findings, B-value and resazurin test, are complementary.…”
Section: Nanoparticle Heating Capabilitymentioning
confidence: 70%
See 1 more Smart Citation
“…We evaluated the cell viability of HeLa cells with varying concentrations 1.5, 3, 6 and 12 nM by resazurin tests and using a real-time monitoring system ( Table 2) demonstrated that the NPs are expected to be ingested by cells via receptor-mediated endocytosis. 59 The results of the B-values obtained from the real-time cell viability measurements are between 3 × 10 −5 s −1 and 7 × 10 −5 s −1 , indicating high cell biocompatibility compared with the results of Yang et al 39 The B-value findings are in the range of PEGylated Au NPs of the same size which are known to be biocompatible. Both test findings, B-value and resazurin test, are complementary.…”
Section: Nanoparticle Heating Capabilitymentioning
confidence: 70%
“…Thus, a damping coefficient, here referred to as a B-value is an indication for amplitude damping rate in order to quantitatively describe cell viability. In the method, which means the real-time, label-free monitoring system of cell viability mentioned above, 39 HeLa cells were allowed to attach onto an oscillating AFM cantilever (SNL-10, k = 0.12 N m −1 , f 0 = 23 kHz, Bruker Corporation). For that purpose, a drop of 100 µL of HeLa cell solution surrounded the installed cantilever, while the AFM was driven in Intermediate Mode at a given frequency of 22 kHz, so that the cell sediment eventually attaches to the surface of the cantilever.…”
Section: Real-time Monitoring Of Cell Viabilitymentioning
confidence: 99%
“…It must be noted that conventional and NMS assays monitor different metabolic parameters. In most conventional analyses, the MIC is identified by the bacterial ability to replicate, while for the NMS, this concentration is associated with the reduction of the sensor's fluctuations, associated with alterations in the bacterial membrane elasticity (36,37) or to their internal metabolic activity. Indeed, while the information is similar, the concentration at which one or the other phenomenon occurs can be different.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the technique enables the detection of energy consumption of a few ATP molecules, as demonstrated in previous works using finite elements mod-eling or studying conformational changes in quaternary protein structures (31,33). Thus, the NMS can been used to evaluate the fluctuations of a very limited number of viable specimens (single mammalian cells or tens of bacteria) (32,(34)(35)(36)(37).…”
mentioning
confidence: 95%
“…In addition, investigation on the toxicity of nanostructures and biointeractions rely on data from a wide variety of experiments with several different methods and techniques that are chosen on the basis of laboratory capabilities and researchers´ technical expertise [21,22]. Then, there are, as today, no standard cell panels or defined protocols available for assessment of cancer cell responses to NPs; therefore, data arising from those studies are difficult to compile and integrate.…”
Section: The Selective Toxicity Of Nanomaterials On In Vitro Cancer Cmentioning
confidence: 99%